Basic Principles of Health-Related Quality of Life in Parents and Caregivers of Pediatric Surgical Patients with Rare Congenital Malformations—A Scoping Review - Witt, Stefanie; Blömeke, Janika; Bullinger, Monika; Dingemann, Jens; Quitmann, Julia (European Journal of Pediatric Surgery, 2020)
Introduction The diagnosis of a rare congenital malformation with necessary surgical treatment is an emotionally stressful event in a parent's life and may impact parental health-related quality of life (HrQoL). We aimed to review the literature on HrQoL in parents and caregivers of pediatric surgical patients with rare congenital malformations and summarize the results.Materials and Methods For this scoping review, a literature search in PubMed was conducted from inception to November 21, 2019. Inclusion and exclusion criteria to select articles were defined a priori.Results Four articles (published 2014–2018) describing HrQoL in parents of pediatric surgical patients with rare congenital malformations in comparison to population-based references or healthy control groups were identified. Only European studies were found, and sample sizes varied between 15 and 87 participants. Results for parental HrQoL yielded inconsistencies.Conclusion So far, only a few studies with small sample sizes focus on parental HrQoL in pediatric surgical patients with rare congenital malformations. To gain a comprehensive understanding of the impact of a rare congenital malformation on HrQoL of all family members, it is necessary to consider three main aspects: (1) to use both generic- and disease-specific instruments measuring HrQoL of the young patient as well as his/her parents and siblings in larger sample sizes, (2) to collect longitudinal data, and (3) to consider a mixed-method approach.
Keywords: health-related quality of life; parents; rare diseases; congenital malformations; surgical treatment